Study on the setting characteristics of filling slurry with different aggregate combinations - Deng, Daiqiang; Wang, Ye; Liang, Wei; Fan, Jinkuan (Frontiers in Earth Science, 2023)
To grasp the phase change characteristics of the filling slurry from fluid to solid state in time, conducted a study on the setting characteristics of the filling slurry with different aggregate combinations, and analyzed the law of the initial and final setting time with the change of the amount of cementation powder, filling plant tailings, tailing pond tailings and water. The results show that the initial and final setting time of the filling slurry prepared from the tailings of the filling plant is proportional to the concentration, and is positively correlated with the slope decline of the sand-cement ratio. The filling slurry prepared from the tailings of the tailing pond shows roughly the same change trend as the above slurry, but the change law is not obvious, which cannot be expressed by one kind of functional model, and the initial setting time and final setting time are less than the above slurry, which is because the tailings of the tailing pond contain more fine particles, which play a role in delaying setting in the slurry. For example, for five kinds of filling materials with different aggregates of 4:1, 6:1, 8:1, 12:1, and 20:1 sand-to-ash ratios and concentrations of 66%~72%, the initial setting times of filling slurry prepared from tailings of filling plant and tailings of tailing pond were 75.3h~112.3h, 77.6h~122.2h, and the final setting times were 82.8h~123.4h, 85.5h~ 133.9h. Therefore, it shows that the use of filling plant tailings containing fewer fine particles to prepare filling slurry can obtain a better treatment effect of the mining area, and the shortening of the solidification and hardening process of filling slurry can accelerate the mining cycle operation, and increase the amount of solid waste disposal per unit time, thus creating the necessary technical conditions for the enterprise to improve production efficiency and sustainable development.